Total lactic acid bacteria, microstructure and texture analysis of probiotic soft cheese with rennet-induced protein gelation - Lola Ayu Istifiani; Rahma Micho Widyanto; Iva Tsalissavrina; Windi Jinni Erlita; Bella Agustina Putri Handayani (AcTion: Aceh Nutrition Journal, 2025)
Consumers are becoming increasingly aware of the importance of choosing healthy probiotic-rich functional foods, such as cheese. Total lactic acid bacteria (LAB) is a crucial measure of success in the development of probiotic soft cheese. Furthermore, it is important to analyze the microstructure and texture of products to determine consumer acceptance. In this study, a randomized block design (RBD) was used with four concentrations of Lactobacillus plantarum FNCC 0026 (0%, 5%, 10%, and 20%). Total LAB was quantified using the total plate count (TPC) method. The microstructure and texture were analyzed using field-emission scanning electron microscopy (FESEM) and a texture profile analyzer (TPA), respectively. In this study, 5% concentration yielded the highest LAB count of 8.054 ± 0.54 log CFU/g (2.0 × 108 CFU/g) and optimal texture attributes. The texture values included hardness (32.41–48.89 N), adhesiveness (0.03–2.65 Nmm), and springiness (0.78–0.83). Furthermore, FESEM analysis revealed no differences in the protein and fat distribution in the microstructure of probiotic soft cheese. These results substantiate the potential of probiotic soft cheese as functional foods. A concentration of 5% Lactobacillus plantarum FNCC 0026 yielded optimal results for total LAB count and texture profile attributes, including hardness, adhesiveness, and springiness.